Bolivian Andes : from climate change to human displacements ? - Kaenzig, Raoul (: Eds. Borsdorf, A., Stötter J. and Veuillet, E. Austrian Academy of Science., 2011)
This research explores the impact of climate change on population migration in the mountainous regions of Bolivia. Migration, considered here as an “ex-situ” adaptation strategy, can be chosen to cope with the worsening environmental conditions. In this case-study based research, some preliminary results are presented in order to better understand the weight of perceived climate change impacts on migration decisions. Additionally, some issues related to glacial retreat, especially the visual dimension, are stressed.
, 2011
Keywords: Bolivia; Andes; Migration; Climate Change; Glaciers; Perception